Drug Therapy: An Amphiphilic Ruthenium Polymetallodrug for Combined Photodynamic Therapy and Photochemotherapy In Vivo (Adv. Mater. 6/2017). Issue 6 (February 2017) - Sun, Wen; Li, Shuyi; Häupler, Bernhard; Liu, Juan; Jin, Shubin; Steffen, Werner; Schubert, Ulrich S.; Butt, Hans‐Jürgen; Liang, Xing‐Jie; Wu, Si
Abstract : X.‐J. Liang, S. Wu, and co‐workers demonstrate a redlight‐responsive Ru‐containing block copolymer as a polymetallodrug for phototherapy in article 1603702. This block copolymer self‐assembles into nanoparticles that can accumulate at the tumor sitet. Red‐light irradiation induces release of the anticancer Ru complexes and generates cytotoxic 1 O2, both of which inhibit the growth of cancer cell.